USE OF ARTIFICIAL INTELLIGENCE FOR SOCIAL ENGAGEMENT: THE CASE OF EMBODIED CONVERSATIONAL AGENTS. (11th November 2018) - Demiris, G
Abstract: The emergence of new digital technologies has led to novel approaches to address social isolation and provide companionship for older adults considering the clinical workforce shortage and a frequent lack of social-supportive networks. Embodied conversation agents (ECAs) are interactive applications (digital avatars or three dimensional characters that may be anthropomorphic or resemble a pet or cartoon) utilizing various computational methods including artificial intelligence and machine learning, that engage in conversation in order to provide companionship or even coaching for health. In this presentation we highlight a review of published studies examining the use of ECAs for older adults and report on our pilot study of an ECA system with 10 older adults with mild cognitive impairment who interacted with a digital pet in their home over 3 months. We discuss related opportunities and challenges including issues of autonomy, informed consent, privacy and confidentiality, attachment and potential impact on human relationships.